Isobologram Analysis: A Comprehensive Review of Methodology and Current Research - Huang, Ruo-yue; Pei, Linlin; Liu, QuanJin; Chen, Shiqi; Dou, Haibo; Shu, Gang; Yuan, Zhi-xiang; Lin, Juchun; Peng, Guangneng; Zhang, Wei; Fu, Hualin (Frontiers in Pharmacology, 2019)
Drug combination is a common method for clinical disease treatment. Whether the combination of drugs is reasonable often affects the result of the disease treatment. Many methods have been used to evaluate interaction between drugs to date. Isobologram analysis has been mathematically proven and widely used to evaluate drug interactions. In this paper, the principle of isobologram analysis and its application in drug interaction evaluation are summarized. The applications of the similar cotoxicity coefficient and fractional inhibitory concentration index in the evaluation of drug interaction are also reviewed. This work is expected to evaluate the effect of formulations scientifically and provide scientific judgment standards for the development of formulations and clinical drug compatibility.